Synthesis and Anticonvulsant Activity of 7-Alkoxy-Triazolo-[3, 4-b] Benzo[d]Thiazoles - Deng, Xian-Qing; Song, Ming-Xia; Wei, Cheng-Xi; Li, Fu-Nan; Quan, Zhe-Shan (Medicinal Chemistry, 2010)
The present study describes the chemical synthesis and anticonvulsant activity evaluation of a series of 7- alkoxy-triazolo-[3, 4-b]benzo[d]thiazoles. Most compounds exhibited good anticonvulsant activity in the Maximal electroshock (MES) test. And the structure-activity relationships (SAR) were analyzed. Among the compounds studied, 7- octyloxy-triazolo-[3, 4-b]benzo[d]thiazole (5g) was found to be the most potent compound with a median effective dose (ED50) value of 8.0 mg/kg and a protective index (PI) value of 15.0, possessing better anticonvulsant activity and higher safety than marketed drugs carbamazepine and phenytoin. The mechanism study of compound 5g showed that it displayed broad spectrum activity in several models, and it is likely to have several mechanisms of action (including inhibiting voltage-gated ion channels and GABAergic activity).
Keywords: Bicuculline-Induced